Design and optimization of a flexible arrayed eddy current sensor. (16th February 2017) - Sun, Zhenguo; Cai, Dong; Zou, Cheng; Zhang, Wenzeng; Chen, Qiang
Abstract: The inspection of the hollow axle inner surfaces is a key process to guarantee the safety of high-speed trains. A novel flexible arrayed eddy current sensor was developed to improve the reliability of the non-destructive testing of the hollow axle inner surfaces, whose main innovative aspect was the new design of excitation/sensing traces to achieve a differential and arrayed configuration. Only two independent excitation traces were used in the sensor to induce eddy currents, which can be detected by 16 differential sensing elements. The lift-off effects and the influence of the excitation frequency and geometrical parameters of the proposed sensor was investigated and presented in this paper. Finite element models were built to analyze the effects of each parameter on the sensor response amplitude. Experimental validations were conducted using a representative set of sensors. Results from experiments and simulations were consistent with each other, which showed that the sensor design can substantially suppress the lift-off effects and modifications of the studied parameters can substantially improve the sensor performance.